The Influence of Stimulus Complexity on the Effectiveness of Visual Associative Learning - Eördegh, Gabriella; Tót, Kálmán; Kelemen, András; Kiss, Ádám; Bodosi, Balázs; Hegedűs, András; Lazsádi, Anna; Hertelendy, Ábel; Kéri, Szabolcs; Nagy, Attila (Neuroscience, 2022)
•Stimulus complexity influences the effectiveness in visual associative learning.•More complex visual stimuli could elicit more effective learning.•This more effective learning can be seen by high and low working memory load, too.•The reaction times in equivalence learning were shorter by more complex stimuli.•The retrieval and the transfer were not affected by the stimulus complexity. Visually guided equivalence learning is a special type of associative learning, which can be evaluated using the Rutgers Acquired Equivalence Test (RAET) among other tests. RAET applies complex stimuli (faces and colored fish) between which the test subjects build associations. The complexity of these stimuli offers the test subject several clues that might ease association learning. To reduce the number of such clues, we developed an equivalence learning test (Polygon), which is structured as RAET but uses simple grayscale geometric shapes instead of faces and colored fish. In this study, we compared the psychophysical performances of the same healthy volunteers in both RAET and Polygon test. Equivalence learning, which is a basal ganglia-associated form of learning, appears to be strongly influenced by the complexity of the visual stimuli. The simple geometric shapes were associated with poor performance as compared to faces and fish. However, the difference in stimulus complexity did not affect performance in the retrieval and transfer parts of the test phase, which are assumed to be mediated by the hippocampi.